Transformación agroecológica en el cantón de Mora en Costa Rica y emigración indígena huetar (1900-1955) - Amaris Cervantes, Orlando (Revista de historia., 2016)
This study throws light on the socio-environmental causes of Huetar families’ migration inside the existing Mora canton, Costa Rica, and outside of this canton, in the frst part of the 20th century. It also establishes the relationships between these displacements and Costa Rica peripheral involvement in the world economy between 1900 and 1955.